2017
DOI: 10.1080/02699052.2017.1312018
|View full text |Cite
|
Sign up to set email alerts
|

Circulating extracellular DNA levels are acutely elevated in ischaemic stroke and associated with innate immune system activation

Abstract: These findings suggest that assessment of peripheral blood cfDNA levels may be useful for the identification of ischaemic stroke in the acute care setting, and provide associative evidence that cfDNA is a potential activator of the peripheral innate immune system in response to cerebral ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…ACS is a term encompassing clinical disorders of myocardial ischemia or infarction, and it has been demonstrated that inflammatory responses involving neutrophil activation play a major role in atherosclerotic changes and progression . According to a recent study, circulating extracellular DNA levels in AIS patients are associated with innate immune system activation . Though clear mechanisms are yet to be explored, these processes could lead to the elevated level of NETs in the ACS and AIS groups in this study.…”
Section: Discussionmentioning
confidence: 74%
“…ACS is a term encompassing clinical disorders of myocardial ischemia or infarction, and it has been demonstrated that inflammatory responses involving neutrophil activation play a major role in atherosclerotic changes and progression . According to a recent study, circulating extracellular DNA levels in AIS patients are associated with innate immune system activation . Though clear mechanisms are yet to be explored, these processes could lead to the elevated level of NETs in the ACS and AIS groups in this study.…”
Section: Discussionmentioning
confidence: 74%
“…33,34 Elevated cfDNA might also reflect physiological (e.g., exercise) 35,36 and non-malignant pathological processes, 7 such as inflammation, diabetes, tissue trauma, sepsis, and myocardial infarction. [37][38][39] The concentration of cfDNA in blood varies significantly; it ranges between 0-5 and >1000 ng/ml in patients with cancer and between 0 and 100 ng/ml in healthy subjects. 7,24 There is also a marked variation in blood ctDNA levels among patients with different tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…97 Platelets induce NETosis by releasing thromboxane A2; then, in turn, NETosis leads to thrombin generation. 37,98 Lymphocytes, monocytes, and neutrophils can also release mtDNA strands. 93 In the blood, mtDNA can be present in both particle-associated and non-particle associated forms.…”
Section: Introductionmentioning
confidence: 99%
“…As stated before, an increase in the quantity of cfDNA is not only seen in tumor patients but in other conditions as well. These are (just to mention a few examples) patients with myocardial infarction [150], an ischemic stroke [151], trauma patients [152] and healthy subjects who exercise extensively [153]. Additionally, it was demonstrated that the amount of cfDNA depends on many intrinsic as well as extrinsic factors (such as DNA extraction method, see following text) and that there is large overlap in the quantity of cfDNA in patients with a malignant or benign disease and frequently also with healthy people [154].…”
Section: Is Dna Quantification and Determination Of Cfdna Fragmentatimentioning
confidence: 99%